Fire resistance and reaction-to-fire of Shorea macrophylla and Acacia mangium particleboards treated with boron and phosphorous-based fire retardants - Kamal, Izran; Koh, Mok Poh; Tan, Yu Eng; Abood, Faizah; Ashaari, Zaidon; Puteh, Nordin (Universiti Putra Malaysia Press, 2012)
Fire resistance and reaction-to-fire of Engkabang (Shorea macrophylla) and Acacia mangium particleboards, which were treated with zinc borate (ZBr) and monoammonium phosphate (MAP), were investigated in this study. Ten percent of the fire retardants were incorporated into the particleboards in powder form during resin-particle mixing process. The fire resistance of the boards was assessed using insulation and integrity failures. Meanwhile, reaction-to-fire was conducted to examine the effectiveness of the fire retardants to delay ignition and reduce weight loss. The study showed that ZBr was excellent in improving insulation and integrity failures of the boards as compared to MAP. Zinc borate delayed the increase of unexposed face temperature up to 18 min and reduced the weight loss down to 0.57% (ZBr-treated A. mangium), but MAP was shown to be better than ZBr in delaying ignition (i.e. up to 41s for A. mangium and 20s for S. macrophylla). The ineffectiveness of the fire retardants to reduce weight loss of the boards (MAP-treated and ZBr-treated S. macrophylla and MAP-treated A. mangium might be due to leaching and volatization of phosphoric acid and boric acid in the formulations of the particleboards which would then cause the chemical loading to be lower than the actual chemical loading. It is suggested to extend the research especially in determining the chemical loading of each treated boards during and after they are exposed to fire. This is essential to prove the claim that chemical loading is decreased due to the leaching of phosphoric acid and volatization of boric acid.